2017
DOI: 10.5194/acp-17-10143-2017
|View full text |Cite
|
Sign up to set email alerts
|

CCl<sub>4</sub> distribution derived from MIPAS ESA v7 data: intercomparisons, trend, and lifetime estimation

Abstract: Abstract. Atmospheric emissions of carbon tetrachloride (CCl 4 ) are regulated by the Montreal Protocol due to its role as a strong ozone-depleting substance. The molecule has been the subject of recent increased interest as a consequence of the so-called "mystery of CCl 4 ", the discrepancy between atmospheric observations and reported production and consumption. Surface measurements of CCl 4 atmospheric concentrations have declined at a rate almost 3 times lower than its lifetime-limited rate, suggesting per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 52 publications
4
15
0
Order By: Relevance
“…3, a model VMR(t) is adapted, with the least squares approach, to the time series of the monthly COCl 2 averages. As explained in Valeri et al (2017), the model includes two different offsets for the two mission phases (FR and OR), a common linear term (the trend we are interested in), QBO-and solar flux-related terms and the characteristic atmospheric periodicities of 24, 18, 12, 9, 8, 6, 4, 3 months. Note that the residuals oscillate around zero, except in the first half of 2005 (between 24 th and 36 th month), which corresponds to the transition period between FR and OR mission phases.…”
Section: Phosgene Trendsmentioning
confidence: 99%
“…3, a model VMR(t) is adapted, with the least squares approach, to the time series of the monthly COCl 2 averages. As explained in Valeri et al (2017), the model includes two different offsets for the two mission phases (FR and OR), a common linear term (the trend we are interested in), QBO-and solar flux-related terms and the characteristic atmospheric periodicities of 24, 18, 12, 9, 8, 6, 4, 3 months. Note that the residuals oscillate around zero, except in the first half of 2005 (between 24 th and 36 th month), which corresponds to the transition period between FR and OR mission phases.…”
Section: Phosgene Trendsmentioning
confidence: 99%
“…This is the MIPAS-ESA V7R NOM dataset. The MI-PAS V7 retrievals differ from the MIPAS V5 retrievals in that they use the level-1b radiances version 7 for which a timedependent nonlinearity correction scheme has been adopted to account for the change in nonlinearities over the course of the mission due to the aging of the detectors (Valeri et al, 2017). This correction introduces an altitude-dependent temporal change in the MIPAS retrievals.…”
Section: Relative Instrumental Driftsmentioning
confidence: 99%
“…These values justify the need for studying its potential interference in benzene measurements. It should also be noted that the global average lifetime of TCM reported in the recent literature is 44 years (36-58) (Ko et al, 2013;Valeri et al, 2017), so its effects, such as the one indicated here, will be manifested during the next decades.…”
Section: Introductionmentioning
confidence: 67%
“…In this sense, 9500 Mt of TCM were estimated to be emitted in 192 countries in 2007 (Penny et al, 2010). However, since the entry into force of the Montreal Protocol, there has been a progressive decrease in the environmental presence of TCM, with a decrease in (Valeri et al, 2017). In 2005, the Agency for Toxic Substances and Disease Registry (ATSDR, 2005) determined a global average concentration of 0.7 µg Nm −3 with peaks in urban areas of 1.4 to 4.5 µg Nm −3 , whereas 45 µg Nm −3 was detected in the vicinity of landfills (Brosas-Montecastro, 2008).…”
Section: Introductionmentioning
confidence: 99%